Estudio del nivel operatorio de estudiantes universitarios - Dibar Ure, María Celia; Queiroz, Gloria (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The shadows task proposed by J. Piaget was chosen, after preliminary interviews, to study the level of congnitive operations of university freshmen at Universidad Federal Fluminense, Brazil. We interviewed 82 students of engineering, chemistry and physics using clinical, individual interviews. We discuss the results and possible applications to the teaching of physics at this level.